(untitled) (The Journal of Psychology and Sociology, 2023)
The pandemic of COVID-19 became a very stressful experience for the population. Being unpredict-able and unexplored disease, it brought additional stress and negative impact on people’s psychological and physical functioning as well as well-being. In this study we assumed that mindfulness as a state of mind can become a regulator that helps to reduce negative consequences of perceived stress and aspects of psychophysical well-being: perceiving pain and sleep quality. The main goal of this study is to determine how the level of perceived stress and aspects of psy-chophysical well-being (specifically: sleep quality and perceiving pain in daily life) were interconnected with the level of mindfulness among adult students during the times of pandemic. In October 2021 we questioned 106 adult students with Mindful Attention Awareness Scale (MAAS), Meaning in Life Questionnaire (MLQ), Perceived Stress Scale (PSS), Numerical Pain Rating Scale (NPRS) and Sleep Quality Questionnaire. SPSS Statistics 23 program was used, Pearson’s criteria was applied to investigate the correlations among these parameters. As a result, it was clarified in our sample respondents with higher levels of mindfulness have lower levels of perceived stress and pain as well as better sleep quality. The results of the study complement the body of knowledge in a sphere of interconnections between mindfulness, stress and aspects of psychophysical well-being. Results can be used for further researches in the field of mindfulness, stress, pain, sleep quality, psychophysical well-being in whole, post-covid conditions. In a practical sense results can be helpful in formation of training programs, psychotherapy, educational activities, including stress resistance training, mindfulness practices, post-covid rehabilitation. Key words: perceived stress, chronic stress, pain, mindfulness, well-being, sleep quality, presence.